Selection and Identification of a DNA Aptamer for Multidrug-Resistant Acinetobacter baumannii Using an In-House Cell-SELEX Methodology - Farrel Côrtes, Marina; Marli Bes, Taniela; Ribeiro Deo, Beatriz; Barbosa dos Anjos, Beatriz; Jimenez Galisteo, Andrés; Cerdeira Sabino, Ester; Santos, Carlos; Figueiredo Costa, Silvia (Frontiers in Cellular and Infection Microbiology, 2022)
Infections caused by multi-drug resistant A. baumannii are a worldwide health concern with high mortality rates. Rapid identification of this infectious agent is critical as they can be easily spread and display difficult or no treatment. In this context, the development of reliable and economically viable detection and therapeutic methodologies are still challenging. One of the promising solutions is the development of nucleic acid aptamers capable of interacting with bacteria. These aptamers can be used for specific recognition of infectious agents as well as for blocking their functions. Cell-SELEX technology currently allows the selection and identification of aptamers and is flexible enough to target molecules present in an entire bacterial cell without their prior knowledge. However, the aptamer technology is still facing many challenges, such as the complexity of the screening process. Here we describe the selection and identification of a new aptamer A01 using an in-house methodology, whole cell SELEX-based, against multiresistant Acinetobacter baumannii, with rapid execution and low cost. In addition, this protocol allowed the identification of the aptamer A01 with the whole A. baumannii cell as target. The aptamer A01 demonstrated a binding preference to A. baumanni when compared to K. pneumoniae in fluorescence assays. Although the time kill assay did not show an effect on bacterial growth, the potential bactericidal or bacteriostatic effects cannot be totally discarded. The new categorized aptamer (A01) displayed a significant binding affinity to MDR A. baumannii.